DIGITALISASI DAN PRESERVASI DOKUMEN KELEMBAGAAN PT HAKHARA AKADEMIA INDONESIA BERBASIS WEB: PENDEKATAN HUMANIORA DIGITAL [WEB-BASED DIGITIZATION AND PRESERVATION OF INSTITUTIONAL DOCUMENTS AT PT HAKHARA AKADEMIA INDONESIA: A DIGITAL HUMANITIES APPROACH] - Muhammad Firjatullah Nur Akbar (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2024)
Institutional digitization projects in Indonesia typically stop at providing a file repository, without a standard metadata scheme or long-term preservation strategy, so the result is storage rather than an archive. This study designs and builds a web-based document digitization and preservation system for PT Hakhara Akademia Indonesia using a digital humanities approach. A descriptive qualitative design combined archival appraisal of the full holdings, in-depth interviews with six informants to capture undocumented context, system design mapping the OAIS reference model onto four functional components, and evaluation through timed retrieval across twelve scenarios plus a focus group with eight users. Of 1,013 files appraised, 16.88 percent were damaged, and 47 meeting minutes lacked agenda or attendance records making them uninterpretable without testimony. Dublin Core was extended with three local elements covering creation context, related documents, and narrative notes. Retrieval time fell 90.69 percent on average, yet users valued the narrative notes most, showing that findability and intelligibility require different treatment.